Process : 50 product designs from concept to manufacture. - Hudson, Jennifer, ....- (London : Laurence King, 2008)
This book provides an in-depth study of the creative and manufacturing processes behind 50 contemporary domestic design objects. Chosen from all around the world, they span furniture, lighting, tableware, textiles, and other products. Featuring the work of both long-established and emerging designers, each product is selected for its significant use of new technology, unorthodox or complex production process, use of innovative materials (or traditional materials adapted in new and unexpected ways) and, in some cases, for the creative concept behind it. Beginning with a general introduction, each project is then presented through explanatory text as well as an inspirational image, sketch, detail shots of production processes, and the completed product. A glossary of production methods is also included. Process offers an interesting and useful insight into how products are designed, for students and professional designers alike.
Keywords: Ontwerpen